An analysis of narrative text translation of the children's fable “Seven Crows” - Wulan Anjarwati kusuma (LADU: Journal of Languages and Education, 2023)
Background:  A language translator of literary texts for children is not an easy task, translators of literary works face obstacles in translating the author's moral messages, idiolects, SL cultural boundaries and SL writing styles. Purpose: The purpose of this study is to describe the translation of fairy tale genre children's literature, the translation method used and the quality of the translation of the fairy tale into Indonesian. Design and methods: The research method used is a descriptive qualitative research method. Brothers Grimm's fairy tale, The Seven Crows, became the topic of research. Results: The results of the study show that the Seven Crows fable has more figurative language. Several translation methods used in fables include paraphrasing, adaptation, idiomatic, literal, free, and semantic methods. The method used can maintain the language style of fairy tales in the original language and produce translations that are accurate and easy to read, even though the reception is low.